Toys come home : being the early experiences of an intelligent stingray, a brave buffalo, and a brand-new someone called Plastic - Jenkins, Emily, 1967- (Schwartz & Wade Books, 2011)
When a little girl gets a plush stingray for her birthday, it makes friends with some of her other toys as they all try to navigate in the world of real people.